Noise level response to the number of vehicles at low traffic area Kelantan Highway - Mohd Ismail, Norhashimah (2018)
The study was done to show how noise level responses related to the number of vehicles at low traffic area in Kelantan highway. The main objectives of this study were to analyze the relationship between the number of vehicles and noise level responses during weekend and weekday at Kelantan highway and to determine the effects of noise pollution to the local communities at Kelantan highway. The research conducted in three months times which were April, May and August 2017 and the noise level data was compared to the Department of Environment (DOE) standard. Noise level was recorded using noise level meter (TM102) and manual traffic count method was applied during this study. For the questionnaires design, I had been divided into three sections which were perception, awareness and knowledge about noise pollution towards environment and human health. Questionnaires were distributed to 370 respondents to determine the effects of noise pollution to the local communities living in the adjacent area. It showed that people at the study area were sensitive and alert to noise pollution towards environment and human health. There was a relationship between the noise level responses and trafﬁc volume and this was tested using the Spearman’s test. The test showed the correlation coefﬁcient was O.470* which was moderate association relationship (r=0.470*). Meanwhile, the reliability of respondents about noise pollution by trafﬁc towards local communities exceeded 0.700 which mean that it was acceptable. From the analysis, the noise level response was higher on weekend compared to weekday due to the increasing number of vehicles. The one-way ANOVA result showed (p=0.574), where it was not statistically signiﬁcantly differences between noise and time. Based on the study, it can be concluded that 20% of noise level measurement from the study area exceeded the limit that recommended by DOE which can affected the hearing loss.